+0  
 
+1
40
2
avatar

What is the value of this expression?

 

 May 3, 2020
 #1
avatar+300 
+1

Let's break this up :D

 

There's \(3a^{-3}\)\(b^2\)\(2a^{-1}\) and \(b^0\), where \(a = -2\) and \(b=-3\).

 

\(3a^{-3} = 3((-2)^{-3}) = 3(\frac{1}{(-2)^3}) = \frac{3}{-8} = -\frac{3}{8}\)

\(b^2 = (-3)^2 = 9\)

\(2a^{-1} = 2((-2)^{-1}) = 2(\frac{1}{-2}) = \frac{2}{-2} = -1\)

\(b^0 = 1 \) :D

 

So, our expression is:

 

\((\dfrac{-\frac{3}{8} \cdot 9}{-1 \cdot 1})^2\)

 

Which is: 

\((\dfrac{-\frac{27}{8}}{-1})^2\)

 

Which makes:

\((\frac{27}{8})^2\) 

 

Which equals:

\(\fbox{$\frac{729}{64}$}\)

 

Which is the last option :D

 May 3, 2020
 #2
avatar+657 
+1

Great job showing your steps! Keep it up CentsLord!!!

LuckyDucky  May 3, 2020

18 Online Users

avatar